Targeted Therapy of Tuberculous Meningitis in Rats with Methylprednisolone Composite Nanoparticles: Targeted Therapy of TBM in Rats with MPS-NPs - Dai, Chuanyang; Guan, Xianyue; Qin, Guannan (Cellular and Molecular Biology, 2022)
It was to investigate the targeted therapeutic effect of methylprednisolone (MPS) composite nanoparticles (NPs) on tuberculous meningitis (TBM) in rats. A total of 180 special pathogen-free (SPF) Sprague Dawley (SD) rats (male) were randomly and equally assigned to the normal control group, TBM infection group, and TBM treatment group. Those in the TBM infection group and the TBM treatment group were injected with Mycobacterium tuberculosis suspension via the tail vein. After the TBM model was established, rats in the TBM treatment group were injected intraperitoneally with methylprednisolone-nano sterically stabilized liposomes (MPS-NSSLs), and those in the normal control group were injected with an equal amount of normal saline. MPS-NSSLs were prepared, and their quality evaluation, encapsulation rate, drug-lipid ratio, and stability were detected. The particle size distribution of MPS-NSSLs was 95.4 ± 0.7 nm, showing a complete spherical structure, and the encapsulation rate was 91.24 ± 0.27 %, and the drug-lipid ratio was about 0.4. After 7 days of treatment, the water content of brain tissue in the TBM infection group was drastically superior to that in the control group (P<0.05); Evans blue (EB) content in the TBM infection group was dramatically superior to that in the control group (P<0.05). The TBM rat model was successfully established, and this model verified that MPS-NSSLs had the characteristics of high efficiency and low toxicity in the treatment of TBM rats.